Description of Dental and Oral Health Self-Care Behavior Against Disease Pulp in Pulpitis Patients at the Kassi Kassi Community Health Center - Feblina, Ayu Rahayu; AR, Aisyah; Eni, St. Nur; R, Risman Abdi; Ropida, Ita (International Journal of Health Sciences, 2023)
Introduction: Dental and oral diseases that many Indonesians suffer from are supporting tissue disease and dental caries, the source of these two diseases is due to neglect of dental and oral hygiene. In carious teeth or cavities that are not treated, they will slowly reach the pulp and cause pulp inflammation and pain which is known as pulpitis. Objective: To determine dental and oral health self-care behavior at the Kassi-Kassi Health Center. Method: This type of research is quantitative research, with a sample of 32 people taken using accidental sampling technique. Results: The majority of respondents had poor dental and oral health self-care behavior (59%) and the number of respondents affected by pulp disease in the acute category was greater than respondents who were not affected by pulp disease in the Pulp Hyperemia (HP) and Chronic Pulp categories with a percentage of pulp disease in the category Acute pulp was (50.0 %) while HP was (18.8 %) and chronic pulp was (31.2 %). Conclusion: Dental and oral health self-care behavior against pulp disease in pulpitis patients at the Kassi-Kassi Health Center is still not good, so pulpitis patients are more likely to suffer from pulp disease with acute pulp category (50.0%).